Design and fabrication of a device to characterize the electromechanical behavior of Superconducting Nb3Sn 3-strand cables under transverse load. - Derman, Konstantin. (2017)
Abstract: Nb3Sn superconducting wire is currently in use in the Toroidal Field (TF) and Central Solenoid (CS) coils of the ITER fusion machine because of its ability to remain in the superconducting state at the high magnetic fields required to confine a plasma. However, this conductor is sensitive to strain, which degrades its electromagnetic performance. In the past 15 years, a lot of research has been focusing on the understanding of the mechanisms behind the degradations due to bending, transverse, and axial strains. This thesis work focused on the design, fabrication and preliminary functionally tests of a mechanical system to apply transverse load on a 3-strand Nb3Sn cable. The design of a completely new loading mechanism has been developed to apply transverse load to the 3-strand cable and the device has been fabricated. The mechanism is designed so that a load cell and an extensometer are used to record vertical load and displacement respectively. This information is used to evaluate the transverse load applied to the sample. The mechanism allows an overall transverse deformation of the cable from a 1.78 mm to a 1.16 mm diameter. The mechanism is designed to sustain and react transverse forces up to 60 kN on a cable length of ~215 mm. Finite Element Analysis (FEA) was performed using Solidworks Simulation to confirm the structural integrity of the mechanism and preliminary tests were performed to verify the operational functionality of the device.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Luisa Chiesa.; Committee: Douglas Matson, and Makoto Takayasu.; Keyword: Mechanical engineering.